Implementing The Multimodal Communication Modes On Telegram Bot ELIA - I Gusti Ngurah Adi Rajistha; Dewa Ayu Kadek Claria (Center of Language and Cultural Studies [CLCS], 2023)
Information related to lectures in a study program must be conveyed clearly and carried out regularly. Even though the information has been delivered routinely and centrally, students sometimes miss the announcement. This condition causes the need for a more effective method of accommodating FAQs (frequently asked questions) so that students can find information related to lectures, proposal exams, thesis exams, and other information related to study programs. This study aims to implement four essential components in the multimodal communication model in conveying information in the English Literature Study Program, Faculty of Letters, Universitas Warmadewa in providing fast and accurate information. This research is field research located in the English Literature Study Program, Faculty of Letters, Universitas Warmadewa. The data sources are documents and policies in the English Literature Study Program. Data were collected from academic guidelines, proposal & thesis guidebooks, academic calendars, curriculum, and other documents that support the educational process at the English Literature Study Program. FAQs were collected through interviews with the Head of the English Literature Study Program. This study shows the use of textual modes organized in categories to connect commands and information in the database.